Hydrogen/oxygen premixed combustion characteristics in micro porous media combustor. (15th December 2015) - Pan, J.F.; Wu, D.; Liu, Y.X.; Zhang, H.F.; Tang, A.K.; Xue, H.
Highlights: Effect of several parameters on combustion characteristics of micro porous media combustor was investigated. Porous media material with low Cp and high thermal conductivity leads to better temperature distribution on the wall. The highest emitter efficiency occurs at ϕ  = 0.8, though the highest mean temperature occurs at ϕ  = 1.0. The interaction between flow velocity and porosity has strong impact on temperature gradient and pressure drop. Abstract: The micro-combustor is a major component of the micro thermophotovoltaic (TPV) system. In order to improve the stability of combustion and efficiency of the micro-TPV conversion device, porous media combustor was designed. Porous media combustion can increase flame stability and gain higher conversion efficiency compared with the free flame combustor. In this work, the influence of several major parameters on micro combustion, namely material of porous media, hydrogen to oxygen equivalence ratio, porosity of porous media and mixture flow rate were investigated using the numerical simulation method. Results indicate that, even though at three different equivalence ratio conditions, SiC is still one of the most suitable porous media materials. Besides, high flow velocity and big porosity both induce high temperature gradient and big pressure drop. The interaction between these two parameters plays an important role in external wall temperature. Analyses in this paper reveal that with the appropriate parameters: ϕ  = 0.8, v  = 6 m/s, porosity is 0.5 and porous media material is SiC, micro combustor with porous media structure could greatly increase combustion efficiency. Present research will facilitate the optimization and improvement of micro-TPV conversion device.